Does psychopathy differentially predict treatment-seeking during incarceration versus postrelease?. Issue 3 (19th May 2018) - Schrader, Shannon W.; Tangney, June P.; Stuewig, Jeffrey B.
ABSTRACT: The notion that high psychopathy inmates seek treatment for nontherapeutic reasons is frequently assumed but lacking empirical evidence. In a sample of 217 jail inmates, we examined whether psychopathy differentially predicted treatment-seeking during incarceration versus postrelease. Overall, analyses revealed psychopathic inmates did not artificially seek treatment at a higher rate than their lower-psychopathy peers during or following incarceration. There was no evidence psychopathy was associated with treatment-seeking for present-oriented reasons during incarceration. High psychopathy inmates, particularly Factor 1, were more likely to request jail law library access than their lower-psychopathy peers. These findings challenge assumptions regarding psychopathic offenders' treatment-seeking behaviors.